Campur Kode dalam Tuturan Masyarakat Kelurahan Terusan Baru Kecamatan Pangkalan Kerinci Kabupaten Pelalawan - Yulita, Erna (UIR PRESS, 2022)
Subdistrict, Pelalawan Regency. code mixing in the speech of the community of Terusan Baru Subdistrict, Pangkalan Kerinci, Pelalawan Regency? (2) what are the factors that cause code mixing events in the speech of the community of Terusan Baru Village, Pangkalan Kerinci Regency, Pelalawan Regency? the occurrence of code-mixing events in the speech of the community of Terusan Baru Village, Pangkalan Kerinci District, Pelalawan Regency.The theory used in this study is the theory of Abdul Chaer (2010: 116-117) and Nababan (1991: 32).The method used in this study is ad is a qualitative method. The results of the research found are 1) the form of code mixing in the speech of the community of Terusan Baru Village, Pangkalan Kerinci District, Pelalawan Regency: code mixing in the form of words, phrases and clauses, and 2) Factors causing code mixing events in the speech of the community of Terusan Baru Village, Pangkalan Kerinci District. Pelalawan Regency is (a) Relaxation or informal situation, (b) there is no clear expression, and (c) showing off their learning. Examples of code-mixing sentences in the form of words;